Prevalencia del consumo de estimulantes por parte de estudiantes universitarios y factores asociados. - Morales-Méndez, Adriana; Espinoza-Céspedes, Magalis; Franz-Chacón, Melanie; Solano-Garita, Natalia; Campos-Arroyo, Ximena; Alfaro-Mora, Ramsés (Revista de Salud Pública)
Objective To identify the prevalence of stimulant use among the student population at the Universidad Latina de Costa Rica, San Pedro Campus, and some factors associated with these habits. Materials and Methods this is an analytical observational cross-sectional study conducted at the Universidad Latina de Costa Rica, San Pedro Campus. Surveys aimed at students of the different university careers were used as an instrument to collect information. The statistical analysis was carried out with SPSS 19 software Results The average age of university students was 20.6 years, and the most commonly used stimulants were soft drinks and coffee. There is a significant difference among men and women regarding the consumption of nicotine-containing products. More than 50% of the university population surveyed was enrolled in Health Sciences programs. Conclusions Sex, marital status, work status, academic level, the faculty in which the students are enrolled, and the province of residence are not factors that influence the use of stimulants by the university population of the Universidad Latina de Costa Rica. The only exception was nicotine consumption and its relationship to the sex of the individual.